Determinan Ekspor Komoditas Karet Indonesia Ke Amerika Serikat Periode 1990-2022 - Rifki Khoirudin; Moch Izzal Azizi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Indonesia's rubber exports have always been dominated by the United States as the largest exporting country throughout the year. Recently, rubber exports to the United States have decreased along with the decline in rubber production in Indonesia. The purpose of the study was to analyze the influence of Indonesian rubber production variables, Indonesian rubber land area, Indonesian rupiah exchange rate against the United States dollar, Indonesian inflation rate, United States GDP on Indonesian rubber export variables to the United States. The type of data used is secondary data with time series data for the period 1990-2022. The analytical tool used in this study uses the Error Correction Model (ECM). The results of this study in the long-term and short-term relationship simultaneously showed that the rubber production variable, the variable area of Indonesian rubber land, the Indonesian rupiah exchange rate against the United States dollar, the Indonesian inflation rate, and the United States GDP had a significant effect on Indonesian rubber exports to the United States. Partially in the long term and short term relationship shows that the variable production of Indonesian rubber has a positive and significant effect on Indonesian rubber exports to the United States, while the variable area of Indonesian rubber land, the Indonesian rupiah exchange rate against the United States dollar, the Indonesian inflation rate, and the United States GDP is not significant to Indonesian rubber exports to the United States. Keywords: Export, Production, Land Area, Exchange Rate, Inflation, GDP.